Evaluation of institutional change mechanisms of domestic chain hotels in turkey in terms of service type - BÖRÜ, MELİHA DENİZ (My University, 2022)
The idea that institutions are static and difficult to change, which was widely accepted in the early periods of institutional theory, has been replaced by the view that institutions can also change and even this change may not be in the direction of isomorphism. Institutional logics, which are frequently examined in institutional theory studies and accepted as the source of diversity and contradictions in the organizational field, have brought a different perspective to the field. The critical effect of institutional logics on the behavior and decisions of organizations has made it important to investigate the factors that lead to changes in institutional logics. In this context, the four mechanisms that affect the change in institutional logics are entrepreneurial, structural overlap, event sequencing and conflicting institutional logics. It is an indisputable fact that the tourism industry, which has an important share in the service sector, provides a significant advantage to the countries that can use its potential and especially affects the economies of these countries positively. It is important to examine the change in their institutional logic in order to understand and explain the behavior patterns of hotels, which have a high share in accommodation businesses, which are one of the most important elements of the service sector. In this study, the mechanisms behind the institutional logic change of local chains were examined through interviews with 8 hotel managers reached through voluntary participation from local chain hotels in Turkey. Another aim of the study is to investigate the relationship between the differentiation of domestic chains in terms of the service they provide and the mechanisms that affect the institutional logic changes. The interviews were analyzed with the MAXQDA 2022 qualitative data analysis program. In this study, findings related to the mechanisms that cause changes in the institutional logic of resort hotels, which are predominantly leisure tourism, and city hotels, which provide predominantly business tourism, are included.
Keywords: Chain Hotels; Service Type; Instutional Change